Penerapan Pembelajaran Berbasis Proyek Pada Matakuliah Matematika Diskrit untuk Meningkatkan Keterampilan Mahasiswa dalam Memanfaatkan Struktur Diskrit dalam Menyelesaikan Masalah - Yurinanda, Sherli; Rozi, Syamsyida (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2023)
Graduate Learning Outcomes (CPL), structured in the learning plan, require student-centered learning and the role of the lecturer as a facilitator known as Student-Centered Learning (SCL). One learning model that facilitates students to fulfil CPL is the PjBL (Project Based Learning) model. The purpose of this research is to achieve the vision and mission of the study program, which is to improve the quality of education in the learning process through the achievement of CPL. Discrete Mathematics is a course that provides fundamental material in computational science and a mathematical foundation for other courses that require programming. Therefore, the PJBL learning model was applied to the Discrete Mathematics course in this study, addressing mathematical problems and supporting the fulfilment of CPL in the course. This research approach is qualitative, involving activities, and quantitative in student responses after learning using the PjBL model. Research activities have three stages: preparation, implementation, and final. The research subjects were two classes of Semester 3 Mathematics study program students with 59 students. In the learning process using the PjBL model, there are two projects that students have implemented, and based on a questionnaire distributed to students, the majority of students feel that the implementation of PjBL is suitable for the Discrete Mathematics course.